2017
DOI: 10.1177/0194599817739295
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Anatomy of the Tensor Fold and Anterior Attic

Abstract: Objectives The objectives of the study were to (1) study the anatomical variations of the tensor fold and its anatomic relation with transverse crest, supratubal recess, and anterior epitympanic space and (2) explore the most appropriate endoscopic surgical approach to each type of the tensor fold variants. Study Design Cadaver dissection study. Setting Temporal bone dissection laboratory. Subjects and Methods Twenty-eight human temporal bones (26 preserved and 2 fresh) were dissected through an endoscopic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
9
0
5
Order By: Relevance
“…It was a complete plate in 46.5%, pyramidal projection in 32.6%, while it was not visualized in 20.9% of temporal bones. Li et al [10] had found a cog in all their studied patients with ME disease revealing complete and rudimentary types only. The "complete" type was most commonly seen (89%).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…It was a complete plate in 46.5%, pyramidal projection in 32.6%, while it was not visualized in 20.9% of temporal bones. Li et al [10] had found a cog in all their studied patients with ME disease revealing complete and rudimentary types only. The "complete" type was most commonly seen (89%).…”
Section: Discussionmentioning
confidence: 92%
“…The height of this bony plate was 1.5 to 3.0 mm, and when complete, it is seen to extend from the facial canal wall to the scutum [29]. The cog is considered a dividing landmark between the anterior and the posterior epitympanic compartments, while the Tensor Tympani mucosal fold (TTF) is subdividing the anterior epitympanic compartment into anterior epitympanic recess (AER) and supra-tubal recess (STR) [10]. Commonly, a vertical type of TTF (mucosal fold) is attached to the cog, and if this TTF is complete, the ventilation to anterior epitympanic recess can be blocked.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations